Therapeutic potential of an anti-CCR9 mAb evidenced in xenografts of human CCR9+ tumors - Santamaria, Silvia; Delgado, Marisa; Botas, Marta; Castellano, Eva; Corraliza-Gorjon, Isabel; Lafuente, Paloma; Muñoz-Calleja, Cecilia; Toribio, Maria L.; Kremer, Leonor; Garcia-Sanz, Jose A. (Frontiers in Immunology, 2022)
Relapsed or refractory T acute lymphoblastic leukemia (T-ALL) still carries poor prognosis. Aiming to improve outcomes, the therapeutic potential of an anti-CCR992R monoclonal antibody (mAb 92R), targeting the human chemokine-receptor CCR9 is analyzed on orthotopic xenotransplants. 92R mAb treatment of mice carrying human CCR9+ T-ALL cell lines or primary T cell leukemias inhibits tumor growth and increases survival. The therapeutic effects of 92R are specific and synergize with chemotherapeutic agents increasing survival. Furthermore, 92R decreases size of non-hematopoietic tumors with a forced CCR9 expression and of solid tumors generated by the pancreatic adenocarcinoma cell line AsPC-1. In addition, a humanized version of 92R mAb (Srb1) is also able to inhibit growth of CCR9+ T-ALL tumor cells in vivo, increasing survival 2.3-fold. Finally, 92R mAb prevents liver metastasis accumulation of infiltratesformation and reduces tumor cell numbers in already formed metastasesinfiltrates. Thus, the humanized version of 92R mAb (Srb1), displays therapeutic potential for CCR9+ tumor treatment and might represent one of the first therapeutic antibodiesy for precision medicine on T-ALL patients